2014
DOI: 10.1007/s00395-014-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin-1 facilitates toll-like receptor 3 signaling in human endothelial cells

Abstract: Endothelial cells are important elements in the vascular response to danger-associated molecules signaling through toll-like receptors (TLRs). Flotillin-1 and -2 are markers of membrane rafts but their true endothelial function is unknown. We hypothesized that flotillins are required for TLR signaling in human umbilical vein endothelial cells (HUVECs). Knockdown of flotillin-1 by shRNA decreased the TLR3-mediated poly-I:C-induced but not the TLR4-mediated LPS-induced inflammatory activation of HUVEC. As TLR3 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…By contrast, wild-type conidia did not show different phagocytosis rates because these conidia via their DHN-melanin layer most likely already disturbed flotillins in the membrane forming the phagocytic cup. In line, recently it was shown that flotillin-1 facilitates inflammatory toll-like receptor 3 signaling in human endothelial cells (Fork, Hitzel et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…By contrast, wild-type conidia did not show different phagocytosis rates because these conidia via their DHN-melanin layer most likely already disturbed flotillins in the membrane forming the phagocytic cup. In line, recently it was shown that flotillin-1 facilitates inflammatory toll-like receptor 3 signaling in human endothelial cells (Fork, Hitzel et al, 2014).…”
Section: Discussionmentioning
confidence: 78%
“…SCARA4 has previously been shown to be expressed in mammalian epithelial cells [28]. Although its ability to bind dsRNA is not yet elucidated in rainbow trout, SCARA4 is likely a surface receptor for dsRNA in mammals [10,33]. It is not however a surface receptor for acLDL in mammals [34] and neither could acLDL bind SCARA4 (CL-P1) in zebrafish [11].…”
Section: Discussionmentioning
confidence: 95%
“…An involvement of flotillin-1 and -2 in modulating the content of caveolin-1 and annexin-2 in exosomes has also been indicated [55]. Notably, other studies suggest that changes of the exosomal content of caveolin-1 can follow changes of its synthesis at the endoplasmic reticulum that is affected by flotillin-1 [13], as described below.…”
Section: Flotillin-mediated Endocytosis Requires Protein S-palmitoylamentioning
confidence: 86%
“…A contribution of flotillin-1 to proper functioning of the endoplasmic reticulum has also been indicated by studies of Fork et al [13] yet without addressing the role of its S-palmitoylation. Those authors found that a downregulation of flotillin-1 but not of flotillin-2 with shRNA led in human umbilical vein endothelial cells to a reduction of the level of several other proteins, including caveolin-1.…”
Section: Some Unique Functions Of Flotillin-1 Are Determined By Its Smentioning
confidence: 96%
See 1 more Smart Citation